Effect of dietary lipid saturation on layer production and egg quality - King, Ernest John (University of the Free State, 2012)
A study was conducted to investigate the effects of dietary lipid saturation on nutrient digestibility, egg production and egg quality characteristics of laying hens during peak production (≤ 42 weeks of age). Five isoenergetic (12.6 MJ AME/kg DM) and isonitrogenous (170 g CP/kg DM) diets were formulated with a 30 g/kg lipid inclusion level, using a blend (50 / 50) of fish- and linseed oil (control n-3), pure fish oil (polyunsaturated n- 3), sunflower oil (polyunsaturated n-6), high oleic acid (HO) sunflower oil (monounsaturated n-9) and tallow (saturated fatty acid treatment). The blend of fish- and linseed oil blend were used to increase the α-linolenic acid content of the control n-3 diet, while fish oil was used in the polyunsaturated n-3 diet to increase the concentration of eicosopentaenoic- (EPA) and docosahexanoic acid (DHA) fatty acids primarily. Sunflower oil and HO sunflower oil was used to increase the linoleic- and oleic acid in the polyunsaturated n-6 and monounsaturated n-9 diets respectively, whereas tallow was used to increase palmitic- and stearic acid levels in the saturated fatty acid (SFA) treatment. Two hundred, individually caged Hy-Line Silver Brown hens (20 weeks of age) were randomly allocated to the five dietary treatments (n = 40 replicates/treatment) and received the respective experimental diets. During 24, 28, 32, 36 and 40 weeks of age, all eggs produced were recorded, individually weighed and used for analysis of internal and external egg qualities. While feed intake of hens was measured weekly, body weights were determined monthly. Data for the respective collection weeks were pooled for calculation of parameter means during statistical analysis. During the mentioned weeks eggs were evaluated for shell quality and internal egg quality. During week 30 of age, 12 eggs per treatment were also randomly selected for analyses of fatty acid methyl esters (FAME), thiobarbituric acid reactive substances (TBARS) and peroxide value (PV) while another 12 eggs were stored at 4oC for analyses after 28 days. At the end of the study (42 weeks of age) six birds per treatment were used to determine the effects of dietary lipid saturation on nutrient digestibility. Dietary lipid saturation had no effect (P > 0.05) on feed intake as well as most of the nutrient digestibility coefficients, except in the case of crude protein (P < 0.05) and fat (P < 0.0001), whereby the monounsaturated n-9 diet resulted in the highest (P < 0.05) CP digestibility which differs statistically only with that of the polyunsaturated n-6 diet, but not with any of the other dietary treatments. Therefore, no clear influence of dietary lipid saturation on apparent digestibility of CP could be detected. Furthermore, all poly- and monounsaturated diets had a higher fat digestibility (94.2 to 95.6%) than the SFA diet (90.4%). Although both the polyunsaturated n-6 and control n-3 treatments had the lowest (P < 0.01) apparent metabolisable energy (AME) and AME corrected for nitrogen (AMEn) values, no clear trend regarding dietary lipid saturation on nutrient digestibility could be established. Similarly to nutrient digestibility results, dietary lipid saturation resulted in a limited significant response on production parameters tested without any recognisable trends. The SFA treatment resulted in the lowest (P < 0.015) percentage sellable eggs, while feed efficiency (P < 0.001) and percentage eggshell (P < 0.05) was the lowest for the monounsaturated n-9 and polyunsaturated n-6 treatments respectively. Evaluating internal egg qualities, the control n-3 and polyunsaturated n-3 treatments had the lowest (P < 0.0001) egg yolk colour compared to that of the SFA which resulted in the highest colour score. Additionally, the FAME of egg yolk was successfully altered to represent that of the particular dietary treatment without any detrimental effects on the total fat content (P = 0.24), fat free dry matter (P = 0.17) or moisture (P = 0.66) content of egg yolk. The polyunsaturated n-3 treatment was highly effective (P < 0.0001) in increasing the EPA and DHA concentration of egg yolk, whereas a general increase in the dietary n-3 content resulted in a decreased (P < 0.0001) ratio of n-6 / n-3 for both the control n-3 and polyunsaturated n-3 diets. Both the SFA and monounsaturated n-9 treatments resulted in the lowest (P < 0.0001) TBARS for both time periods, whereas the polyunsaturated n-3 treatment resulted in the highest (P < 0.001) TBARS for both fresh and stored eggs (0.27 mg malonaldehyde / kg yolk during both time periods). From the results of the current study it can be concluded that although fat digestion was lower for the SFA treatment, AME values did not differ between treatments. With the exception of the SFA treatment that resulted in less sellable eggs, no influence of lipid saturation on egg production and external egg shell qualities could be detected. The results showed that PUFA n-3 diets could be successfully used to enrich the essential n-3 fatty acids of eggs. However, lipid oxidation stability as well as yolk colour was negatively influenced by an increase in PUFA n-3 type fatty acids.

‘n Studie is uitgevoer om die effek van dieet lipiedversadigheid op nutriëntverteerbaarheid, eierproduksie en kwaliteitseienskappe van eiers gedurende piekproduksie (≤ 42 weke ouderdom) van lêhenne te ondersoek. Vyf energie- (12.6 MJ SME/kg DM) en proteïenekwivalente (170 g/kg RP DM) diëte is geformuleer. In die onderskeie diëte is 30 g/kg lipiedbronne ingesluit deur van ‘n vis- en lynsaadoliemengsel (50 / 50) as kontrole n-3 behandeling, visolie (polie-onversadig n-3), sonneblomolie (polie-onversadig n-6), hoë oleïensuur (HO) sonneblomolie (mono-onversadig n-9) en beesvet (versadige vetsuur dieet) gebruik te maak. ‘n Mengsel van vis- en lynsaadolie is gebruik om die α-linoleїensuur inhoud van die kontroledieet te verhoog, terwyl die visolie in die polie-onversadige n-3 dieet gebruik is om eikosapentanoë (EPA) en dokosaheksaenoë (DHA) vetsure te verhoog. In die polie-onversadige n-6 en mono-onversadige n-9 diëte is sonneblomolie en HO sonneblomolie gebruik om onderskeidelik die linoleensuur en oleïensuur inhoud in die onderskeie diëte te verhoog. Beesvet is gebruik om die vlakke van palmitien- en steariensuur in die versadige vetsuur dieet te verhoog. Twee honderd Hy-line Silwer Bruin henne (20 weke oud) wat in individuele hokke aangehou is, is ewekansig tussen die vyf behandelings (n=40 herhalings/behandeling) verdeel. Gedurende ouderdomsweke 24, 28, 32, 36 en 40 is eierproduksie daagliks aangeteken, eiers individueel geweeg en na die laboratorium vir verdere analise van eksterne- en interne kwaliteitseienskappe geneem. Voerinname is weekliks bepaal, terwyl die henne se liggaamsmassa gedurende die genoemde weke bepaal is. Data van dié onderskeie weke is vir statistiese doeleindes saam gepoel en is gedefinieerd as die piekproduksie periode. Die eierdop- en interne kwaliteit van die eiers wat geproduseer is, is in bogenoemde weke geëvalueer. Gedurende ouderdomsweek 30 is 12 eiers van elke behandeling ewekansig geselekteer om vir oksidasie stabilitiet d.m.v. peroksied waarde (PW) en tiobarbituursuur reaktiewe bestandele (TBARS) te toets. ‘n Verdere 12 eiers is ewekansig gekies en in ‘n yskas (4oC) vir 28 dae gestoor waarna dit vir beide parameters ontleed is. ‘n Veteringstudie is aan die einde van die studie uitgevoer (42 weke ouderdom) om die effek van vetsuurversadigheid op nutriënt verteerbaarheid te evalueer. Daar was geen effek van vetsuurversadigheid (P > 0.05) op voerinname en die skynbare verteerbaarheid van die meeste nutriënte nie, behalwe in die geval van RP en vet waar die mono-onversadigde n-9 dieet die hoogste (P < 0.05) RP verteerbaarheid gehad het wat slegs met dié RP verteerbaarheid van die polie-onversadigde n-6 dieet verskil het. Al die polie- en mono-onversadigde diёte (vanaf 94.2 tot 95.6%) het ook ‘n hoёr (P < 0.0001) vetverteerbaarheid gehad as die versadigde vetsuur dieet (90.4%). Alhoewel die polieonversadige n-6 en kontrole behandeling beide die laagste (P < 0.01) skynbare metaboliseerbare energie (SME) en SME gekorrigeerd vir stikstof (SMEn) waardes gehad het, was daar geen duidelike verwantskap tussen vetsuurversadigheid en nutriëntverteerbaarheid nie. Daar was ook geen effek van vetsuurversadiging op produksie van die henne nie. Die versadigde vetsuur dieet het statisties betekenisvol (P < 0.015) minder bemarkbare eiers geproduseer. Die doeltreffendheid van voerbenutting (P < 0.001) en die persentasie eierdop (P < 0.05) was onderskeidelik die laagste vir die mono-onversadige n-9 en polie-onversadige n-6 behandelings. Evaluering van interne eierkwaliteite het getoon dat die kontrole n-3 en polie-onversadige n-3 behandelings die laagste eiergeel kleurtelling gehad het in vergelyking met die hoogste (P < 0.0001) kleurtelling van die versadigde vetsuur behandeling. Verder was dit duidelik dat die vetsuurprofiel van die eier deur dieet manipulering suksesvol verander is om die profiel van die dieet te verteenwoordig sonder dat daar enige negatiewe uitwerking op die totale vetinhoud (P = 0.24), vetvrye droë massa (P = 0.17) of voginhoud (P = 0.66) van die eiergeel voorgekom het. Die doeltreffendheid (P < 0.0001) van die polieonversadige n-3 behandeling was duidelik sigbaar met die verhoging in EPA en DHA in die eiergeel en tesame met die kontrole n-3 behandeling het die merkbare verhoging in n-3 inhoud daartoe gelei dat ‘n drastiese verbetering (P < 0.0001) in die verhouding van n-6 / n-3 voorgekom het. Die TBARS vir beide mono-onversadig n-9 en versadigde vetsuur behandelings was die laagste (P < 0.0001) vir beide tydsperiodes, waarteenoor die polieonversadige n-3 behandeling die swakste (P < 0.0001) TBARS (0.27 mg malonaldehied / kg eiergeel) vir beide tydsperiodes getoon het. Daar is tot die slotsom gekom dat alhoewel die vetverteerbaarheid van die versadigde vetsuur behandeling die laagste was, het die SME waardes nie tussen behandelings verskil nie. Met die uitsondering van die versadigde vetsuurbehandeling wat die minste bemarkbare eiers gehad het, is geen invloed van lipiedversadigheid op eierproduksie en eksterne eierkwaliteit waargeneem nie. Die resultate het getoon dat polie-onversadige n-3 diëte met sukses gebruik kan word om essensiële n-3 vetsure in die eier te verhoog. Daarenteen is lipiedoksidasie en ook die kleur van die eiergeel negatief beïnvloed deur polie-onversadigde n-3 vetsure.
Dissertation (M.Sc.Agric. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2012
Keywords: Egg products industry; Eggs -- Production; Dietary supplements; Lipids